Di-n-octyl phthalate degradation by a halotolerant bacterial consortium LF and its application in soil. Issue 17 (29th July 2021) - Wang, Yangyang; Zhan, Wenhao; Liu, Yidan; Cheng, Shanshan; Zhang, Chaosheng; Ma, Jianhua; Chen, Runhua
ABSTRACT: Di- n -octyl phthalate (DOP), a plasticizer used in many different industrial products, is a frequently observed pollutant in the environment. Biodegradation by microorganisms is considered to be a realistic choice for the remediation of DOP contamination. In the present research, the halotolerant bacterial consortium (LF) enriched in our previous research was used to degrade DOP. It was found that the optimal conditions for LF to degrade DOP was temperature 30 o C, pH 6.0, inoculum size >5%, and salt content <3%. LF could degrade a high concentration of DOP (2000 mg/L) with the removal efficiency of 96.33%. Substrate inhibition analyses indicated that the inhibition constant, maximum speciﬁc degradation rate and half-saturation constant were 2544.6 mg/L, 0.7 d −1 and 59.1 mg/L, respectively. Based on the analysis of the gas chromatography-mass spectrometry (GC-MS), the biodegradation pathway for DOP by LF was proposed. Furthermore, LF could degrade DOP in soil (100 mg/kg) with the highest removal efficiency of 89.3%. This study is the first report on DOP biodegradation by bacterial consortium. These results suggest that LF can be used to remediate DOP-contaminated environment. GRAPHICAL ABSTRACT: UF0001